Prevalence of Eimeria spp. in goats from northern Paraná, Brazil - Carla Adriele Rodrigues; Jonas Correia de Araujo Júnior; Jorgeana Guadanhini Negrizolli; Maria Júlia Papin Filadelfo; Mateus Siqueira Pyles; Ana Carolina Cavalieri; Luiz Daniel de Barros; Fernando de Souza Rodrigues; João Luis Garcia (Revista Brasileira de Parasitologia Veterinária)
Abstract This study aimed to evaluate the presence, identify Eimeria species, and epidemiological aspects associated with the infection in goat herds in northern Paraná, Brazil. A total of 384 fecal samples were collected from goats of different breeds, ages, and sexes from eight farms. An epidemiological questionnaire about rearing system (semi-intensive or intensive), age of the animals (up to 6 months or over 6 months), and type of floor in the pen (dirt or slatted) was used to evaluate the epidemiological aspects associated with Eimeria spp. infection. The McMaster technique was used to count Eimeria spp. oocysts. After oocyst counting, the samples were separated for sporulation and species identification. In total, 82.3% (316/384) of the samples showed positive results. For OPG, 37% of the animals exhibited counts >1,000 OPG (max.63600 OPG), whereas 63% had counts <1,000 OPG. Animals from semi-intensive production systems had high oocyst counts (mean-2139 OPG). Goats raised in pens with slatted floors (mean-1158 OPG) have lower average oocyst counts than those raised in facilities with dirt floors (mean-2714 OPG). Eight Eimeria species were identified E. arloingi (23.9%), E. apsheronica (19.7%), E. ninakohlyakimovae (14.3%), E. alijevi (12%), E. caprina (10%), E. jolchijevi (9%), E. hirci (6.9%) and E. christenseni (4.2%). This study showed a high prevalence of Eimeria spp. in goats in northern Paraná, Brazil.